Determinants of Customer Satisfaction in the Digital Banking Ecosystem: An Empirical Study on BYOND by BSI Users - Aliefah, Aniesatun Nurul (IAIN Kudus, 2026)
This study aims to investigate the factors influencing customer satisfaction in the digital banking ecosystem by examining the effects of online transaction experience, trust, and service quality among BYOND by BSI users. This research employed a quantitative approach using non-probability sampling techniques. Data were collected through questionnaires distributed via Google Forms to BYOND by BSI users at Bank Syariah Indonesia KCP Gombong Kebumen and got 92 respondents. The data were analyzed using multiple linear regression with IBM SPSS Statistics 27. The findings reveal that online transaction experience and service quality have a positive and significant effect on customer satisfaction, while trust does not significantly influence customer satisfaction among BYOND by BSI users. These results indicate that customers place greater emphasis on practical digital banking experiences and service performance than on trust factors in evaluating their satisfaction. Therefore, Bank Syariah Indonesia is recommended to continuously enhance the quality of digital services, improve user experience, and develop innovative features that meet customer needs to strengthen customer satisfaction in the digital banking environment.